FENOMENA TREDING IN INFLUENCE DALAM TINDAK PIDANA KORUPSI TANTANGAN PENEGAKAN HUKUM DAN PEMERINTAHAN INDONESIA - Kolono, Sucipto; Widjajanti, Ermania (Ensiklopedia Education Review, 2024)
Abstract: The phenomenon of "Trading in Influence” in corruption crimes is a major challenge for law enforcement in Indonesia. The method in writing is Normative looking at legislation, norms, court decisions and expert opinions. the absence of specific regulations in the Indonesian legal system to ensnare perpetrators of “Trading in Influence.” This paper looks at how this legal weakness allows corruption involving influence to continue without effective sanctions, and explores legal reform solutions to strengthen Indonesia's anti-corruption legal framework. This practice involves individuals or groups utilizing the influence of their power, either as public officials or external parties, to influence government decisions for personal gain. Although Indonesia has ratified the United Nations Convention Against Corruption (UNCAC), regulations related to influence peddling have not been fully accommodated in the law. This study highlights the importance of legal reforms that can ensnare all actors who are outside the Government but are involved in influencing Public policy in order to close loopholes and legal gaps, in order to minimize the adverse impact of corruption on public trust and public welfareKeywords: Corruption, Corruption Crime, Treding in Influence